A terapia ocupacional como profissão : confrontos, condições sociais de exercício e perfil profissional - Soares, Taís Bracher Annoroso (2022)
This thesis, entitled “Occupational Therapy as a profession: confrontations, social conditions of exercise and professional profile”, analyzes the Occupational Therapy profession regarding the reality presented in the State of Sergipe. Its central object is to examine the social conditions of organization of this profession, the various forms of training and access, and more specifically, it examines: how the process of configuring Occupational Therapy as a profession occurred and how someone becomes an occupational therapist, with emphasis on the Sergipe reality. Studying about professions is a subject dealt with by Sociology, with emphasis on the Sociology of Profession. Another focus is on the role of professionalization and the State, the major legislator and employer of this profession. We also address the specific issues of the profession, its definition, identity, shadowing with other professions, the definition of it being a female profession and specific training in the area. Data were collected through a self-administered questionnaire directed at occupational therapists in Sergipe. Among the results, we highlight that, for the reality in Sergipe, the profession is under construction, with young female professionals, who maintain more than one employment relationship, with the State as the main employer, presenting a trajectory of social ascension in relation to their family group. However, if they wish to achieve the so-desired social recognition, issues of identity and shading must be resolved, assuming an associative and political role that will guarantee greater knowledge and social acceptance.